2005
DOI: 10.1007/s00277-004-1003-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of autologous stem cell transplantation for Hodgkin’s disease (HD) and low-/intermediate-grade B non-Hodgkin’s lymphoma (NHL): a report from the Austrian Stem Cell Transplantation Registry (ASCTR)

Abstract: Between 1990 and 2001, 68 patients with advanced Hodgkin's disease (HD) and 86 patients classified as low-/intermediate-grade B non-Hodgkin's lymphoma (NHL) were reported to the Austrian Stem Cell Transplantation Registry (ASCTR). Following autologous stem cell transplantation (SCT) for HD, overall survival was 56% [95% confidence interval (CI): 40-72%] with a disease-/progression-free survival of 49%, reaching a plateau at 5 years. Using multivariate Cox regression analysis BEAM conditioning (carmustine, cyta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13] Unlikely; effects of gender, bone marrow involvement at diagnosis, histology, conditioning regimen, origin of stem cells, mobilization regimen, year of transplantation and immunotherapy were not analyzed in our study. Patient numbers were not enough for making a comparison between groups for some parameters.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13] Unlikely; effects of gender, bone marrow involvement at diagnosis, histology, conditioning regimen, origin of stem cells, mobilization regimen, year of transplantation and immunotherapy were not analyzed in our study. Patient numbers were not enough for making a comparison between groups for some parameters.…”
Section: Discussionmentioning
confidence: 94%
“…Nachbaur et al 6 found OS was 56% with a disease-/ progression-free survival of 49% following AH-SCT. Majhail et al 21 found OS at 10-years 77%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[29][30][31] Exclusion criteria were a history of allergy to aprepitant or FOS, use of aprepitant during the evaluation period, and pregnancy.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%